Facile synthesis of CoFe2O4 nanoparticles and application in removal of malachite green dye. Issue 3 (9th January 2019) - Jinendra, Usha; Kumar, Jeethendra; Nagabhushana, B M; Raghu, Anjanapura V; Bilehal, Dinesh
Abstract : The adsorption capacity of the surface of cobalt ferrite (CoFe2 O4 ) nanoparticles as an adsorbent was investigated. Malachite green dye in aqueous solution was used as the model compound. Various dosages of cobalt ferrite nanoparticles (0·01–0·07 g) were used to determine the capacity to adsorb malachite green. Characterisation of cobalt ferrite was performed using scanning electron microscopy and X-ray diffraction. An adsorbent loading value of 0·07 g, initial dye concentration of 10 parts per million and pH of 10 were used in the evaluation. The maximum amount of dye was absorbed from the solution within 60 min after the start of every experiment. The equilibrium concentration and the adsorption capacity at equilibrium were determined using three different sorption models, namely, Langmuir, Freundlich and Temkin isotherms. It was found that dye adsorption onto cobalt ferrite follows the Langmuir isotherm. The absorption kinetics were found to be of second order.